Investigation of Bacteria Associated with the Spoilage of Zobo Drink Fortified with Scent Leaf and Ginger - F. O. Ibitoye; A. M. Oyetayo; O. K. Aribisala; O. E. Giwa (Archives of Current Research International, 2017)
Aim: This study was aimed at investigating the bacteria responsible for the spoilage of “zobo” a Nigerian non-alcoholic beverage fortified with scent leaf and ginger. Methodology: The plant materials were air dried and grinded mechanically then incorporated into the zobo milieu produced using traditional procedures. Afterwards, the samples were stored at room temperature and in the refrigerator for 5 days and microbial analyses carried out on the samples at 24 hours intervals using pour plate technique. Results: The microbial load of the various zobo samples during storage revealed that there was no significant difference (p≤0.05) between the counts encountered on all the samples as the count ranged from 3.10 x 103cfu/ml (refrigerated sample) to 4.02 x 103cfu/ml (control) on day 0. There was a significant (p≤0.05) increase in the bacterial load on the control sample while those fortified with ginger and scent leaf respectively remained fairly constant throughout the storage. Furthermore, six bacteria species were isolated from the freshly prepared zobo and during storage, they were Bacillus subtilis, Staphylococcus aureus, Micrococcus luteus, Proteus vulgaris, Streptococcus species and Escherichia coli. Out of these, S. aureus, P. vulgaris and B. subtilis persisted in the stored zobo samples during the storage period. Conclusion: From the foregoing, there is can be safely concluded that S. aureus, P. vulgaris and B. subtilisare the main spoilage organisms of zobo drink and ginger as well as scent leaf may not be suitable to curtail the spoilage that may be caused by these organisms in zobo drink.